EFEKTIVITAS PENERAPAN DIRECT MARKETING PADA PENJUALAN REKENING RENCANA TABUNGAN HAJI (RTJH) BANK SINARMAS SYARI’AH MALANG - Eridany, Athallah Noval; Waluyowati, Nur Prima (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
Banks as service business actors in the financial sector, also need the right marketing strategy to be able to reach the target market they want. Bank Sinarmas Syari'ah Malang seeks to market and offer products for the Hajj Savings Plan Account (RTJH) to the public, especially Muslims by conducting direct marketing. The choice of a direct marketing strategy raises the question why Bank Sinarmas Syari'ah Malang prefers to use a direct marketing strategy compared to other marketing strategies. This study aims to determine the effectiveness of implementing direct marketing strategies in selling products for the Hajj Savings Plan Account (RTJH) of Bank Sinarmas Syari'ah Malang. The theory used to support this research is a theory related to marketing and direct marketing. The object of this research is Bank Sinarmas Syari'ah Malang. This study uses a qualitative descriptive approach which uses primary data through interviews, observation and documentation. The data analysis technique used in this research is data triangulation where there is data reduction, data presentation and conclusion drawing. The results of this study indicate that the application of direct marketing strategies to product sales of the Hajj Savings Plan Account (RTJH) can be said to be effective.